I can’t answer u I need to see the graph
Answer:
2.006
Step-by-step explanation:
2*1 = 2. To this you are adding 6 thousandths, or 0.006. Together, you have 2.006 (standard form).
Hi there!
![- \frac{1}{3} + 4 + \frac{2}{3} =](https://tex.z-dn.net/?f=%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%2B%204%20%2B%20%20%5Cfrac%7B2%7D%7B3%7D%20%20%3D%20)
First we rearrange the sum in order to add both of the fractions first. We can rearrange because the only thing we need to do is adding.
![- \frac{1}{3} + \frac{2}{3} + 4 =](https://tex.z-dn.net/?f=%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%2B%20%20%5Cfrac%7B2%7D%7B3%7D%20%20%2B%204%20%3D%20)
Add the fractions.
** If you don't get this, think of this story: you lack 1/3 of an apple pie and someone gives you 2/3 of pie. How much pie do you have left?
- 1 / 3 + 2 / 3 = 1 / 3 **
![\frac{1}{3} + 4 =](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B3%7D%20%20%2B%204%20%3D%20)
Finally add 4 to our found fraction.
![\boxed{ 4\frac{1}{3} }](https://tex.z-dn.net/?f=%5Cboxed%7B%204%5Cfrac%7B1%7D%7B3%7D%20%7D)
Therefore, the answer is 4 1/3.
A postulate isn't required to be proven